THEORETICAL FOUNDATIONS OF ORGANIZING MILITARY PEDAGOGICAL TRAINING FOR CADETS (American Journal of Pedagogical and Educational Research, 2024)
This article expresses an opinion on modern views, problems and solutions for organizing the military-pedagogical process of cadets of higher military education.